Image intensity histograms as imaging biomarkers: application to immune-related colitis. (30th September 2021) - Huff, Daniel T; Ferjancic, Peter; Namías, Mauro; Emamekhoo, Hamid; Perlman, Scott B; Jeraj, Robert
Abstract: Purpose. To investigate image intensity histograms as a potential source of useful imaging biomarkers in both a clinical example of detecting immune-related colitis (irColitis) in 18 F-FDG PET/CT images of immunotherapy patients and an idealized case of classifying digital reference objects (DRO). Methods. Retrospective analysis of bowel 18 F-FDG uptake in N = 40 patients receiving immune checkpoint inhibitors was conducted. A CNN trained to segment the bowel was used to generate the histogram of bowel 18 F-FDG uptake, and percentiles of the histogram were considered as potential metrics for detecting inflammation associated with irColitis. A model of the colon was also considered using cylindrical DRO. Classification of DRO with different intensity distributions was undertaken under varying geometry and noise settings. Results. The most predictive biomarker of irColitis was the 95th percentile of the bowel SUV histogram (SUV95% ). Patients later diagnosed with irColitis had a significantly higher increase in SUV95% from baseline to first on-treatment PET than patients who did not experience irColitis (p = 0.02). An increase in SUV95% > + 40% separated pre-irColitis change from normal variability with a sensitivity of 75% and specificity of 88%. Furthermore, histogram percentiles were ideal metrics for classifying 'hot center' and 'cold center' DRO, and were robust to varying DRO geometry and noise, and to the presence of spoiler volumes unrelated to the detection task. Conclusions. The 95th percentile of the bowel SUV histogram was the optimal metric for detecting irColitis on 18 F-FDG PET/CT. Image intensity histograms are a promising source of imaging biomarkers for clinical tasks.